Sårbarhetsanalys av lax (Salmo salar) i Klarälven med avseende på vattenkraftens påverkan - Elvingson, Kåre (Karlstads universitet, Fakulteten för hälsa, natur- och teknikvetenskap (from 2013), 2024)
Atlantic salmon (Salmo salar) are found in a range of locations along Sweden's coastline, but Sweden's largest lake, Vänern, also harbors a population of salmon; the rare freshwater migratory form. The majority of the salmon in Lake Vänern migrate upstream in River Klarälven in order to spawn, where they are assisted by humans through the "trap and transport" method to get past Klarälven's eight hydropower dams, which otherwise constitute definite obstacles to upstream migration. When the salmon later migrate downstream to Lake Vänern they receive no assistance and experience a high mortality rate as they are partially forced to swim through the turbines. The wild salmon population today includes over 1000 spawners annually, an increase from <200 in the 196os, but far below historic records of over 10,000 spawners. This report therefore aimed to investigate the population growth rate and extinction risk for the salmon in Klarälven, both in the current situation and with passages installed past the hydropower plants, and in doing so answer the questions 1) How large is the population growth rate and risk of extinction for today’s population of salmon in Klarälven over the course of 100 years? and 2) How would passage solutions past the hydropower plants in Klarälven affect the population growth rate and risk of extinction for today’s population of salmon in Klarälven over the course of 100 years? These questions were answered by running a population viability analysis in the program Extinction Vortex, which allows the programming of model populations and the manipulation of parameters to test different scenarios. The scenarios that were tested were 1) Scenario 1: Today's method with trap and transport and total lack of passages, 2) Scenario 2: Trap and transport continues, and downstream passages are installed past all eight power plants, and 3) Scenario 3: Upstream and downstream passages are installed past all eight power plants and trap and transport ceases. The results of the vulnerability analysis did not ...